Pembentukan Akhlak Siswa melalui Perspektif Keagamaan, Adat atau Pembiasaan Siswa di MTsN 4 Lima Puluh Kota - Wenni, Osriza; M, Iswantir; Jasril, Jasril (AHKAM, 2023)
The formation of student morals describes how to direct and improve the behavior, character and attitudes of students from bad to good and become a habit for students in everyday life. At present there is a lot of moral decline among teenagers, especially students or students, such as the low manners of students talking to teachers, lack of mutual respect among friends (bullying), low awareness of carrying out congregational prayers at the prayer room, lack of social boundaries between female and male students. Therefore it is necessary to form or redirect the morals of students. The method that the author uses in discussing this research is a qualitative research method with a descriptive approach, the research location is at MTsN 4 Fifty Kota. In this study the researchers found that there was a decline in morals in students, to overcome the decline in student morals, it is necessary to redirect the attitudes and behavior of these students, one of which is through instilling religious values how to get along in Islam, explaining how customs in the association of adolescents in society and habituation in carrying out commendable morals in everyday life.